Giant ovarian cyst complicating term pregnancy, a rare case report - Caglar Helvacioglu (Medicine Science, 2022)
Adnexal masses are generally detected in the early stages of pregnancy with the assistance of ultrasonographic evaluations. It is rare event for these masses to grow into enormous sizes. Giant cysts can be misdiagnosed as polyhydramnios or intraabdominal ascites. In our case, which was referred to us with the prediagnosis of polyhydramnios, we observed a giant cystic mass originating from the right ovary. We performed right salpingo-oophorectomy during the cesarean section for its management. Pathological examination revealed benign mucinous cystadenoma. The diagnosis and management of adnexal masses should ideally be conducted before pregnancy. Masses reaching the immense sizes during pregnancy can complicate pregnancy, and their management should be specific/personalized to the cases. [Med-Science 2022; 11(1.000): 413-5]